Identifying the factors affecting financial toxicity status in patients with middle and advanced colorectal cancer: a cross-sectional study - He, Xiaofang; Chen, Jie; Zhang, Lin; Li, Qiuping; Zhu, Xiaoli; Zhao, Jie; Chen, Ying (Frontiers in Public Health, 2024)
Background: Colorectal cancer (CRC) ranks as the second most prevalent type of cancer in China. The financial implications of treatment are a significant factor to be taken into account for patients diagnosed with middle and advanced stages of colorectal cancer (III-IV CRC).The research aims to explore current financial toxicity (FT)conditions and analyze factors that may influence it in patients with middle and advanced CRC .Method: This is a cross-sectional survey. The participants of the study were individuals diagnosed with middle and advanced colorectal cancer who were admitted to the hospital between January and June 2023.The cross-sectional survey utilized a variety of instruments, including a general information questionnaire, a cancer patient report outcome economic toxicity scale, a medical coping style questionnaire, an Anderson symptom assessment scale, a disease shame scale, and a social support scale. Multiple linear regression analysis was employed to examine the factors influencing FT.Result: A cohort of 264 patients diagnosed with stage III-IV CRC were included in the study.The majority of patients with intermediate and advanced CRC (87.1%, n = 230) reported experiencing substantial financial strain. Multivariate analysis revealed that factors influencing FT included low family monthly income, out-of-pocket expenses, unemployment, undergoing surgical treatment, the level of stigma, and the severity of symptoms (P < 0.001).Patients with stage III-IV cancer (CRC) demonstrate increased levels of financial toxicity (FT), a common occurrence in individuals with moderate to severe CRC. In patients with stage III-IV CRC, the presence of FT is correlated with various factors including family monthly income, medical payment methods, work status, surgical treatment, stigma levels, and symptom severity. These characteristics may serve as influencing factors for subsequent treatment decisions.